Memperkuat Kearifan Lokal Islam Melalui Perang Obor - Aliva Rosdiana; Ahmad Saefudin (Proceedings of Annual Conference for Muslim Scholars, 2018)
Local wisdom is owned by each region as a part of community culture inherited from generation to generation. The Torch War, as a part of Jepara community culture, is a traditional ceremony that is routinely held every Monday Pahing, at Dzulhijjah month in Tegalsambi village, Tahunan, Jepara. It is called Torch War because the torch is used as a tool to attack each other so that it sparks very large. Sparks from torches are believed to be repellent reinforcements and are able to bring health. In addition, this celebration is a form of gratitude for the abundant harvest that is realized through the alms earth. In the development of tradition, this torch war undergoes a change from pre-Islamic that was originally functioned to repel the forces of evil spirits that bring disease outbreaks to the Islamic period in which the ceremony is used as a venue for syiar Islam that can be seen from the symbols used are two wooden swords and a drum as a relic of Sunan Kalijaga which presented symbols of the power of Islamic syiar. This method used qualitative approach with Islamic culture by doing investigation and interaction among people surrounded. By strengthening local wisdom and prayer as a form of gratitude to Allah SWT in the torch war, the people of Jepara instilled religious values ​​and pride in cultural heritage.